Leveraging sustainable infrastructure for resilient communities : selected papers from the International Conference on Sustainable Infrastructure 2021, December 6-10, 2021 - Bloom, Michael F.; Reddy, Krishna R. (American Society of Civil Engineers, 2022)
Includes 13 peer-reviewed papers on best practices in sustainability. Topics include: sustainable water supplies; residential land development and urban planning; flood risk reduction and coastal protection; energy production and transmission; and infrastructure technologies. This collection will be of interest to engineers, researchers, and public policy officials involved in the development, delivery, and operation of public infrastructure.